Airflow patterns and particle deposition in a pediatric nasal upper airway following a rapid maxillary expansion: Computational fluid dynamics study. Issue 1 (31st December 2023) - Valerian Corda, John; Emmanuel, Jeny; Nambiar, Supriya; K, Prakashini; Zuber, Mohammad
Abstract: The airflow behaviour and particle deposition before and after the maxillary expansion are evaluated using the computational fluid dynamics method. A pediatric patient was subjected to maxillary expansion and the CT scans of pre and post were recorded. The procured CT scans were developed into 3D models using Materialise MIMICS 21.0 (Materialise, Ann Arbor, MI). The analysis was performed using ANSYS FLUENT 2020 R2 with three different flow rates defined at the nostril inlet as 5, 10, and 15 LPM. The surface area and nasal volume increased by 5.1% and 16.5%, respectively, for the post-maxillary expansion case. The velocity profiles show a maximum value at the nasal valve regions followed by a decreased velocity in the mid-nasal region with an 85% lower velocity observed at the nasal valve for the post-maxillary expansion case. The nasal resistance and pressure drop decrease by 46% to 66% in post-maxillary expansion cases. The maximum WSS at the nasal valve region is observed which is reduced by around 47% for post-maxillary expansion cases. Particle deposition studies show a reduction in particle depositions in post cases indicating a greater number of inhaled particles reaching the lungs. The pressure drop and the nasal resistance values were reduced by more than 50% for post-maxillary expansion. The particle deposition studies show increased depositions at higher flow rates for both cases.